Towards practical private information retrieval from homomorphic encryption - Zhuravlev, D. (Algebra and Discrete Mathematics, 2015)
Private information retrieval (PIR) allows a client to retrieve data from a remote database while hiding the client's access pattern. To be applicable for practical usage, PIR protocol should have low communication and computational costs. In this paper a new generic PIR protocol based on somewhat homomorphic encryption (SWHE) is proposed. Compared to existing constructions the proposed scheme has reduced multiplicative depth of the homomorphic evaluation circuit which allows to cut down the total overhead in schemes with ciphertext expansion. The construction results in a system with O(logn) communication cost and O(n) computational complexity for a database of size n.